Postcompulsory Education and Training in China - Wang, Qi (International Higher Education, 2010)
The recent debate on building a learning society in China has focused on the gap between individuals' learning motivation and the government's policy orientation on further developing postcompulsory [i.e., postsecondary] education and training programs through certified learning. This gap, reflecting China's cultural and historical force of credentialism, is believed to be a barrier to the promotion of lifelong learning.